PLAYS IN THE EARLY YEARS: PLAYING AS A PEDAGOGICAL TOOL IN THE TEACHING AND LEARNING PROCESS - Pereira Machado, Thaynni; Maria Freitas Dias Lima, Ana (Revista Gênero e Interdisciplinaridade, 2023)
In this article, we present a studyonthe games in the early years: the ludic as a pedagogical tool in the teaching and learning process, the same discusses the importance of the ludic in the pedagogical practices of theearly years, in order to highlight the beneficial points of the ludic within the school environment. The research hás the following question as problematic: Why use theludic as a pedagogical tool in the early years of elementary school? Given this, work is important because the teaching and learning process needs to be fun and educational at the same time. However, it is necessary for the educator to understand that through playful games, students can learn the most diverse curricular contents, in a creative, fun and pleasant way that promote interaction and socialization between students and students, teachers and students. The overall objective is to understand the importance of play in the early years of elementary school. The methodology was based on a bibliographic study, with data collection through analytical and reflective readings through books, articles, tccs and dissertations. This research is a literature review of a qualitative nature with a descriptive character. Having as a theoretical contribution: Kishimoto (2005), Soares (2020), Rau (2012), Moreira (2017). In view of the bibliographical survey carried out during the development of the project, it is concluded that the ludic collaborates in a beneficial way for the teaching and learning process, as it expands the pedagogical practices of the teacher, favoring the process of acquiring knowledge of the students.